Impact of the Application of Gaseous Ozone on Selected Pathogens Found in Animal Shelters and Other Facilities - Vojtkovská, Veronika; Lobová, Dana; Voslářová, Eva; Večerek, Vladimír (Animals, 2023)
Correctly selecting disinfection procedures is crucial in facilities housing a high number of animals as it directly affects their health. The aim of this study was to verify the virucidal effect of gaseous ozone delivered by commercially available generators under controlled experimental conditions on a selection of viral pathogens (feline coronavirus, canine coronavirus, feline calicivirus, feline parvovirus) commonly found in shelters and other facilities. Two ozone generators with outputs of 3.5 g/h and 20 g/h were used to produce ozone. Virus viability after the application of ozone was evaluated by examining for typical pathogen-specific cytopathic effects on the CRFK (Crandell-Rees Feline Kidney) cell line post-incubation. No cytopathic effect was observed in feline coronavirus after the 2-h application of ozone; in canine coronavirus, the absence of a cytopathic effect was observed after the 4-h application of ozone. The absence of a cytopathic effect in feline calicivirus was observed after the 6-h application of ozone; the viability of feline parvovirus was not impaired even by the 6-h application of ozone. The results of the study confirm lower resistance to the application of gaseous ozone in enveloped viruses.
Keywords: cytopathic effect; ozone generator; pathogen surveillance